2013
DOI: 10.2478/intag-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Some physical properties of ginkgo nuts and kernels

Abstract: Some data of the physical properties of ginkgo nuts at a moisture content of 45.53% (±2.07) (wet basis) and of their kernels at 60.13% (± 2.00) (wet basis) are presented in this paper. It consists of the estimation of the mean length, width, thickness, the geometric mean diameter, sphericity, aspect ratio, unit mass, surface area, volume, true density, bulk density, and porosity measures. The coefficient of static friction for nuts and kernels was determined by using plywood, glass, rubber, and galvanized stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…According to most of the researchers, it was generally observed that the bulk density of nuts was always lower than that of kernels (Kashaninejad et al, 2006). This pattern was similar to that reported in a study on pistachio nuts and kernels (Kashaninejad et al, 2006), ginko nuts and kernels (Ch'ng et al, 2013). This is probably due to the shell, in which the nut is bigger in size than the kernel, hence a decrease in the total mass per unit volume occupied by the nut (Kashaninejad et al, 2006).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…According to most of the researchers, it was generally observed that the bulk density of nuts was always lower than that of kernels (Kashaninejad et al, 2006). This pattern was similar to that reported in a study on pistachio nuts and kernels (Kashaninejad et al, 2006), ginko nuts and kernels (Ch'ng et al, 2013). This is probably due to the shell, in which the nut is bigger in size than the kernel, hence a decrease in the total mass per unit volume occupied by the nut (Kashaninejad et al, 2006).…”
Section: Resultssupporting
confidence: 72%
“…The closer the sphericity to 1.0, the higher the tendency to roll about any of the three axes and the closer the ratio of thickness to width to 1.0, the higher the tendency to rotate with reference to the major axis (Akaaimo and Raji, 2006). Fan palm fruits and seeds have nearly similar and higher sphericity values (0.83 and 0.81, respectively) (Table 1) than fruit, nut and kernel of oil palm (below than 75%) (Akinoso and Raji 2011), ginkgo nuts (69.70%) and kernels (71.86%) (Ch'ng et al, 2013), almond nut (62.96%) and kernels (52.14 %) (Mirzabe et al 2013), cumin (36.2%) and caraway (34.64%) (Zare et al, 2013), and lower than Gbafilo (Chrysobanusicaco) fruits and kernels (0.84 and 0.82, respectively) (Davies and Zibokere, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgo seeds are rich in nutritional components and widely consumed in China by boiling, frying or adding to other foods . However, ginkgo seeds are susceptible to mildew, and they continuously ripen after harvest, leading to high respiration rate and metabolic activity . The loss of quality and restriction during a prolonged storage period are mainly associated with ginkgo seeds' susceptibility to fungal infection and water loss.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to conduct a detailed study of those physical properties of seeds that will facilitate development of effective designs of machines for cleaning and separating the base material from contaminants and seeds of undesirable species. The problem of the physical properties of seeds has been addressed in a number of publications (Anonymous, 2002;Balasubramianian et al, 2012;Ch'ng et al, 2013;Kovalyshyn et al, 2013;Zare et al, 2013). Zaika (2006) discusses issues related to the entire complex of physical properties of plants.…”
Section: Introductionmentioning
confidence: 99%